2006
DOI: 10.1093/cercor/bhj162
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cerebral Reorganization for Auditory Spatial Processing and Auditory Substitution of Vision in Early Blind Subjects

Abstract: Early blind (EB) individuals can recognize bidimensional shapes using a prosthesis substituting vision with audition (PSVA) and activate right dorsal extrastriate visual cortex during the execution of this task. The present study used repetitive transcranial magnetic stimulation (rTMS) to further examine the functional role of this structure in the successful use of the PSVA. Moreover, we investigated which auditory parameter used in the prosthesis (pitch, intensity, or spatial location) might contribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 67 publications
10
128
1
2
Order By: Relevance
“…It is also worth noting that these two regions were also reliably active at an individual level (Table S3). Regarding the right cuneus, our results are in agreement with a previous study of Collignon et al (17) demonstrating that the application of transcranial magnetic stimulation (TMS) over the right superior occipital gyrus (in the vicinity of the right cuneus/superior occipital clusters observed in the present study; see figure 2 in ref. 17) selectively interfered with sound localization abilities in CB, whereas TMS did not interfere with pitch and intensity discriminations in CB and had no effect on any auditory ability in SI.…”
Section: Functional Specialization In the Occipital Cortex Of Cb For supporting
confidence: 94%
See 2 more Smart Citations
“…It is also worth noting that these two regions were also reliably active at an individual level (Table S3). Regarding the right cuneus, our results are in agreement with a previous study of Collignon et al (17) demonstrating that the application of transcranial magnetic stimulation (TMS) over the right superior occipital gyrus (in the vicinity of the right cuneus/superior occipital clusters observed in the present study; see figure 2 in ref. 17) selectively interfered with sound localization abilities in CB, whereas TMS did not interfere with pitch and intensity discriminations in CB and had no effect on any auditory ability in SI.…”
Section: Functional Specialization In the Occipital Cortex Of Cb For supporting
confidence: 94%
“…Regarding the right cuneus, our results are in agreement with a previous study of Collignon et al (17) demonstrating that the application of transcranial magnetic stimulation (TMS) over the right superior occipital gyrus (in the vicinity of the right cuneus/superior occipital clusters observed in the present study; see figure 2 in ref. 17) selectively interfered with sound localization abilities in CB, whereas TMS did not interfere with pitch and intensity discriminations in CB and had no effect on any auditory ability in SI. Regarding the right MOG, our results replicate those of Renier et al (22), who also found this region preferentially active for the processing of spatial over nonspatial nonvisual stimuli in CB.…”
Section: Functional Specialization In the Occipital Cortex Of Cb For supporting
confidence: 94%
See 1 more Smart Citation
“…[27] These fi nding were later confi rmed in studies of subjects with single sensory deprivation (auditory or visual) using neuroimaging techniques with greater spatial resolution (fMRI and PET), [5,[28][29][30] which demonstrated extensive cerebral reorganization in cortical areas, showing how auditory areas of the brain are activated by visual stimuli in deaf persons, [3] while the visual cortex is activated by somatosensory and auditory stimuli in blind persons. [5,28,31,32] Our fi ndings could be ascribed to this form of neuroplasticity, CMP. This would then be confi rmation of results previously obtained in subjects with single sensory deprivation (deaf or blind), well described in review articles.…”
Section: Discussionmentioning
confidence: 57%
“…SIG = sujets témoins voyants ; EBNP = sujets aveugles précoces non performants ; EBSP = sujets aveugles précoces supra-performants (adaptée de [8]). REVUES des sujets aveugles a subi une diminution tandis que celle des voyants est demeurée inchangée [17]. Ce résultat permet donc, pour la première fois, d'établir un lien de causalité entre le recrutement du cortex occipital et la performance associée à une tâche de localisation auditive, démontrant dès lors que l'activité occipitale observée chez les sujets aveugles n'est pas qu'un simple épiphénomène.…”
Section: P3 N1unclassified